Interaction studies of Serendipita indica and Zhihengliuella sp. ISTPL4 and their synergistic role in growth promotion in rice - Sharma, Neha; Dabral, Surbhi; Tyagi, Jaagriti; Yadav, Gaurav; Aggarwal, Himanshi; Joshi, Naveen Chandra; Varma, Ajit; Koul, Monika; Choudhary, Devendra Kumar; Mishra, Arti (Frontiers in Plant Science, 2023)
The current study was conducted to investigate the interaction between the root endophytic fungus Serendipita indica (S. indica) and an actinobacterium Zhihengliuella sp. ISTPL4 (Z. sp. ISTPL4) and their synergistic effect on the growth of rice (Oryza sativa). Both S. indica and Z. sp. ISTPL4 showed positive interaction. Growth of S. indica was observed after inoculation of Z. sp. ISTPL4 on different days and an increased growth of S. indica was observed when Z. sp. ISTPL4 was inoculated at 5 dafi (day after fungal inoculation). Z. sp. ISTPL4 promoted growth of S. indica as an increased spore germination of S. indica was observed in presence of actinobacteria. Furthermore, confocal and scanning electron microscopy (SEM) analysis showed, 27% increase in spore size of S. indica in presence of Z. sp ISTPL4. In LC-MS/MS analysis, increased production of alanine and glutamic acid was observed in their sequential co-culture as compared to individual cultures. Sequential inoculation of S. indica and Z. sp. ISTPL4 significantly increased the biochemical and physical characteristics of rice as compared to their individual inoculum. Biochemical parameters such as chlorophyll content, total soluble sugar, flavonoid content in rice increased up to 57%, 47% and 39% respectively in presence of combined inoculum of S. indica and Z. sp. ISTPL4. To the best of our knowledge, this will be the first study that shows the fungus and actinobacterium interaction and their synergistic role on the growth promotion of rice. The sequential inoculation of S. indica and Z. sp. ISTPL4 will be used to boost the growth of other crops to increase the agricultural yield.